Алгоритм формування беззбитковості сільськогосподарських підприємств - Вініченко, Ігор Іванович; Vinichenko, Igor; Булкін, Сергій Сергійович; Bulkin, Sergey (Дніпровський державний аграрно-економічний університет, 2020)
Вивчення сутнісних основ беззбитковості свідчить про необхідність обов'язкового розмежування виробничих витрат підприємства на змінні й постійні витрати. Дослідження механізму формування беззбитковості потребує моделювання певних економічних ситуацій, які відображають особливий характер залежності беззбитковості від витрат підприємства та виручки від продажу продукції. Досліджено алгоритм формування беззбитковості виробничо-комерційної діяльності сільськогосподарського підприємства та подальшого отримання прибутку для самоокупності й самофінансування як послідовних форм економічної стійкості сільськогосподарського підприємства, який передбачає поетапне визначення межі беззбитковості, самоокупності й самофінансування підприємства. Визначено, що у реальній практичній діяльності сільськогосподарських підприємств він набуває специфічних рис, які обумовлені особливостями аграрної сфери. Встановлено взаємозв'язок беззбитковості з економічною стійкістю підприємства, а також запропоновано інструментарій оцінки беззбитковості, який дозволить своєчасно оцінити поточну економічну ситуацію і обгрунтовувати методи та інструменти забезпечення економічної стійкості ільськогосподарського підприємства. Ensuring the sustainable development of agriculture is central to many of today's problems, due to the key role of the agricultural sector in the socio-economic progress of society. It was established that the provision of economic sustainability of agricultural enterprises decisive role belongs to achieving break-even their industrial and commercial activities. The highest manifestation of economic stability is the ability of the enterprise to develop mainly through its own sources of funding. This ability can be realized only if sustainability and self-financing enterprise. This profitability based on its economic substance, will display zero economic benefit and self-sufficiency and self-financing — in the form of positive income. The identified relationship of break-even with the economic stability of the enterprise, as well as the proposed tools for assessing break-even will allow you to assess the current situation and justify the methods and tools to ensure the economic efficiency of the agricultural enterprise. The study of the essential foundations of breakeven demonstrates the need for mandatory disengagement production costs on variable and fixed costs. Investigation of the mechanism of formation breakeven modeling requires certain economic situations that reflect the special nature of the break-even depending on the cost of the enterprise and revenue from sales. The algorithms of forming breakeven industrial and commercial activity of agricultural enterprises and further revenue for sustainability and self-financing as successive forms of economic sustainability of agricultural enterprises, involving gradual definition limits breakeven self-sufficiency and self-financing company. Determined that in actual practice it acquires farm specific features are due to the peculiarities of agrarian sphere. An algorithm for the formation of break-even point of production and commercial activity of an agricultural enterprise in accordance with the peculiarities of its operation has been developed and proposed. The relationship between break-even and economic stability of the enterprise is established, as well as the tools of break-even assessment are proposed, which will allow timely assessment of the current economic situation and substantiate methods and tools to ensure economic stability of agricultural enterprises.
Algorithm of break-even point formation of agricultural enterprises
Keywords: беззбитковість; break-even; виручка; revenue; затрати; costs; економічна стійкість; economic sustainability; реалізація; sales; ресурси; resources; самоокупність; self-sustainability; самофінансування; self-financing; сільськогосподарське підприємство; agricultural enterprise